HPN Standard of Care and Long-Term Outcomes of CIF Pediatric Patients: Twenty-Eight Years' Experience in a Reference Center - Lezo, Antonella; D'Eusebio, Chiara; Riboldi, Lorenzo; Baldini, Letizia; Spada, Marco (Frontiers in Nutrition, 2022)
Background and aims: Chronic intestinal failure (CIF) therapy changed significantly in recent decades, and both survival and complication rates improved over time. International guidelines claim that early referral of long-term HPN patients to an expert centre with specific standards of care may positively affect long-term outcomes. Herein, we retrospectively analyse the long-term outcomes of a cohort of paediatric patients with CIF followed-up since our Paediatric Intestinal Failure Unit foundation, in 1989. Methods: data of the 120 children followed up at Paediatric Intestinal Failure Unit during the last 28 years were retrospectively collected. Patients’ and HPN characteristics, as well as dependence, survival, and complication rates, were described. Results: Incidence and prevalence of CIF increased during the study period particularly due to the increase of HPN for nondigestive disease (NDD) CIF (47,5% of the study sample). Catheter-related bloodstream infection (CRBSI) rate decreased over the study period: 0,33 episodes/1000 catheters days before 2011 and 0,19 episodes/1000 catheters days afterward. Only 1 patient out of 12 died because of HPN complications. The survival rate of patients with PDD was 98,4% at 1 year from the beginning of HPN, 96,5% at 2 years, and 93,8% from the fifth year onwards. Concerning the dependence rate, 70,6% of patients were still on HPN one year after the start of HPN, 63,7% at 2 years, 52,4% at 5 years, 40,8% from the 9th year onwards, with no significant difference according to the underlying intestinal pathology. The survival rate of NDD patients was 91,2% at 1 year from the beginning of HPN, 87,4% at 2 years, 81,9% from the third year onwards. For what concerns the enteral autonomy, it was regained by 56,7% one year after the start of HPN, 74,5% at 2 years, and 95,0% at the 5th year. Conclusions: Our data confirmed the importance of appropriate standards of care and suggest that applying a specific set of standards and protocols may further improve patients’ outcomes and survival. Indeed, both primary and nondigestive diseases HPN showed good outcomes.